Impact of Variable Seed Rates and Nutrient Regimes on Leaf area index and Yield Characteristics of Late-Sown Wheat Crop (Triticum aestivum L.) - Sidra Qidwai; Rajesh Kumar; A.K. Singh; Abhinandan Singh; Srishti Singh; Lakey Radha; Mitali Kumari Sah; Alok Kumar Pandey (The Bioscan, 2025)
The field experiment was carried out at Agronomy farm, Acharya Narendra Deva University of Agriculture and technology, Ayodhya during Rabi season 2023-24 and 2024 – 2025. The study aimed to evaluate the effect of different seed rates with nutrient management practices on LAI and yield attributes of late sown wheat crop. The experiment followed a split plot design with four treatments in main plot and five treatments in sub plot.